Konstytucyjna wolność pracy - Kuczma, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The introduction highlights the importance of the freedom of labor for people and the development of this freedom in legislation. This is followed by constitutional and international normalization of the freedom of labor based on the example of selected countries. Finally, it characterizes the subject of freedom in Art. 65 of the Constitution, and outlines the essence of the freedom of labor and its limitations. The final part of the article refers to the freedom to work as an individual.
Keywords: wolność pracy; konstytucja